Basil leaf (Ocimmum basillum form citratum) Extract Spray in Controling Aedes aegepty - Wahyuni, Denai; Yulianto, Beny (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
One of the efforts in population control of Aedes aegypti is by fogging, basil leaf is oneof natural insecticide that can be replaced with current chemical one that are commonlyused. Our aim is to measure effectiveness of basil leaf extract on Knockdown time ofAedes aegypti and effective concentration on spray usage. Twenty mosquitoes with sixdifferent intervention, each 5%, 10%, 25%, 50%, positive control, and negative control.All intervention repeated 4 times in every 5 minutes for about 1 hour. The results willbe statistically analysed using one-way ANOVA. Results: concentration of 5% and 10% have KT50 with Insecticide Score of 1 and 2 respectively without any Knockdownconcentration; concentration of 25% have KT50 with Insecticide Score of 3 and WeakKnockdown; concentration of 50% have KT50 with Insecticide Score of 5 and QuickKnockdown. Kruskall-Wallis test p-value=0,000 (p<0,05) with Spearman correlation of+0,87 or 87%. The most effective concentration on Knockdown time of Aedes aegyptiis 50%. In conclusion, Basil extract can be effecctifely used as natural and alternativeinsecticide for fogging.